Measurement of Alkali Metal in Fuel Based on Laser-Induced Breakdown Spectroscopy - Li, Haijian; Chen, Chao; Li, Chi; Zhou, Yuxiang; Wang, Zhenzhen; Yi, Jianhua; Qu, Wengang (Journal of Environmental Accounting and Management, 2026)
Alkali metals (K, Na) in alkali-containing fuels will be released through gasification and combustion during the combustion process. The alkali metals react with oxygen and water vapor in the air to generate oxides or hydroxides, increasing the concentration of particulate matter in the atmosphere. The condensing and depositing alkali metals compounds cause corrosion problems, and affect the normal operation and safety of thermal equipment. Therefore, it is particularly important to study the detection technology for alkali metals. Laser-induced breakdown spectroscopy (LIBS) is widely used in the field of solid fuel detection. In this study, the influence of sample pretreatment methods, laser energy and delay time on the spectral characteristics of alkali metals in mixed samples was studied by LIBS. The experimental results show that as sample is powder, the element distribution is uniform, which is helpful for rapid on-line detection. When the sample is a tablet, the ablation amount of sample is reduced, which reduces the influence of the self-absorption effect of the spectral line. Based on the experimental results of the mixed samples, the solid propellant containing potassium salt was detected. When the laser energy is 60 mJ and the delay time is 1000 ns, the K element in five propellant samples is quantitatively analyzed, and the model shows high analysis accuracy.